Analysis of Stakeholder Orientation for Ecotourism Development in Bali Aga Region, Buleleng-Bali - Putu Agus Haribawa; Ricky Avenzora; Harnios Arief (Media Konservasi, 2017)
Ecotourism development is one of the concrete forms of sustainable tourism, which is currently being developed by both developed and developing countries, such as Bali-Indonesia. Bali Aga Region especially Pedawa Village and Cempaga Village, Buleleng Regency is a potential future area to be developed as ecotourism destination. As a first step to develop ecotourism, it is initially important to know whether or not there is a mutual will among stakeholders for ecotourism development. The purpose of this study is to analyze perceptions and motivations stakeholders in ecotourism development in the area of Bali Aga-Buleleng. Data were collected by questionnaire technique and analyzed by using descriptive analysis. The results of the analysis indicate that the orientation of stakeholders (community and government) in ecotourism development in the Bali Aga region is in a positive dimension and has led to the principle of sustainability. Good perception and motivation indicate that stakeholders have a strong desire to build ecotourism for economic benefits, environmental sustainability and socio-cultural sustainability in Bali Aga region. Keywords: Bali aga, ecotourism, motivation, perception